A Retrospective pharmacoeconomic analysis comparing the cost effectiveness of two treatment groups in patients with complicated intra-abdominal infections - Schmitt, M.E. (My University, 2005)
Many will be disappointed to learn that pharmacoeconomic evaluations provide information, not answers. Although pharmacoeconomics broadens the perspective taken in evaluating drug therapies, the final drug therapy decision is still influenced by clinician preferences, patient desires, and the working and politics of the healthcare delivery system”. 1 Globally and in South Africa there is an increasing pressure on healthcare resources. These pressures have exponents both in the supply and demand arms of the economic equation and have set the scene for the development of a new discipline in healthcare. Pharmacoeconomics can be defined as “the description and analysis of the cost of drug therapy of health care systems and society”. 2 Pharmacoeconomics assesses the ratio of the cost to the consequences of specific drug therapies using a technique called Cost Effective analysis which uses tools such as Cost Minimisation analysis, Cost Effective analysis and Cost Benefit analysis
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements of the degree of Master of Science in Medicine in Pharmaceutical Affairs.
Keywords: Intra-abdominal Infections; Economics, Pharmaceutical; Pharmaceutical